Neonatal Hypoxic-Ischemic Encephalopathy and the Efficacy of Therapeutic Hypothermia: A Systematic Review and Meta-Analysis of Neurological and Survival Outcomes - Jabbar , Rammal Abdul; Memon, Misbah Shirin; Mazhar, Sumaina; Qaisar, Hadiqa; Naqvi , Syeda Sarah; Qureshi , Fareeha Khalid; Rani, Karishma; Naseer, Aamna; Zahid, Aliza; Fatima Amer, Zill-e-Rukh; Mahmood , Abeeha (Indus Journal of Bioscience Research, 2025)
Background: The condition known as neonatal hypoxic-ischemic encephalopathy (HIE) is one of the most crucial complications of neonatal that develops developmental disabilities throughout the world that needs to be addressed. During the last two decades, the application of therapeutic hypothermia (TH) has become one of the accepted protective approaches for babies with moderate to severe HIE in both term and near-term infants. Objectives: Objectives: The goal of this systematic review is to critically analyze the current situation regarding the treatment of hypoxic-ischemic encephalopathy with therapeutic hypothermia in neonates by assessing both its success rate and safety aspects not only that but it’s also render a chance to investigate their impact on survival rates, neurodevelopment outcomes and adverse effects. Methodology: The search involves all three databases of PubMed, Scopus and Google Scholar to collect articles from 2009 through 2025. Additionally, randomized controlled trials along with cohort studies as well as meta-analyses provides the entry criteria for TH investigations on HIE neonates. The authors applies the PRISMA guidelines to perform data extraction and quality assessment. Results: A total of 5,000 neonates participated in the 22 studies that were analyzed. The implementation of therapeutic hypothermia therapy resulted in lower death rates and major neurodevelopmental disabilities among treated patients at their 18-24 months check-up. According to the analyses, the combination of whole-body and selective head cooling treatments resulted in reduced cerebral injury, through findings from MRI and EEG examinations. Mild side effects were noted such as, thrombocytopenia and sinus bradycardia but did not resulted in severe complications. Conclusion: Therapeutic hypothermia proves to be protective and secure intervention for neonates which gives better survival chances with improves developmental results. Therapeutic effectiveness improves when treatment starts before six hours of birth. Studies must continue to evaluate how well therapeutic hypothermia would benefit a number of HIE cases with contexts with limited resources.